Peranan koperasi Syariah dalam meminimalisir ketergantungan masyarakat berhubungan dengan rentenir - Iskandar Johan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2020)
The purpose of this study was to determine the role of Mitra Surya Bahari Islamic Women's Cooperatives in minimizing the dependency people of Aeng Dake village. This type of research is classified into qualitative research using interviews, observation, and documentation to obtain data, then the data is analyzed to obtain conclusions and verification. Based on the findings, the existence of Islamic women's cooperatives in minimizing people's dependence on capital loans from Ribawi financial institutions or from loan sharks is very large. Especially in helping community financing as productive business capital and in meeting household needs. The role of Islamic cooperative is increasingly felt when it becomes a facilitator and acomudator in training and providing counseling to the community to be productive both in agriculture, animal husbandry, and the skill area, both culinary and craft.